Congestion Modelling - C. Robin Lindsey; Erik T. Verhoef (Tinbergen Institute, 1999)
Transportation researchers have long struggled to find satisfactory ways ofdescribing and analysing traffic congestion, as evident from the large numberof often competing approaches and models that have been developed. This paperaims to provide a review of the literature on this topic. The paper startswith the modelling of homogeneous traffic flow and congestion on an isolatedroad under stationary conditions. We set up the supply-demand framework usedto characterize equilibrium and optimal travel volumes. Next, an overview ofmacroscopic and microscopic models of nonstationary traffic flow is given. Wethen describe how trip timing can be modelled, and discuss the essence ofdynamic equilibrium. The paper next reviews the principles of static anddynamic equilibrium on a road network in a deterministic environment, and thenidentifies equilibrium concepts that account for stochasticity in demand andcapacity. Finally, conceptual and practical issues regarding congestionpricing and investment on a network will be addressed.
Keywords: 330; Straßenverkehr; Bottleneck; Theorie